Bai as-salam and e-commerce : a comparative analysis from shariah perspectives - Ainnur Hafizah Anuar Mokhtar; Mohd Zulkifli Muhammad; Tamrin Amboala; Mohd Sarwar E-Alam (2013)
There are worldwide growing concerns among e-commerce customers particularly among Muslims regarding on-line transaction both from technological and Shariah perspectives which require researchers to scrutinize its application into a new dimension. Whilst Bai as-Salam involves transaction by the way the customers up front the payments prior to delivery of the purchased items, e-commerce transactions are carried out through almost similar processes via on line medium. Issues concerning purchasing on-line, the medium of transaction or internet, e-payment mode are among new challenges that require Islamic scholars and researchers to broaden the scope of definition beyond the traditional context. This study sheds light and expands a new definition and tools of Bai as-Salam – as one of many ways of transactions in Islam based on a comparative analytical study between the two concepts of transactions